2017
DOI: 10.1515/ract-2017-2781
|View full text |Cite
|
Sign up to set email alerts
|

Determination of natural radiation levels and lifetime cancer risk in Kırıkkale, Turkey

Abstract: The aim of this study is to determine the levels of background radiation in nine districts of Kırıkkale, Turkey. The outdoor gamma dose rate in the air was measured using a portable digital environmental radiation detector at 170 locations. The mean outdoor gamma dose rate in the air was determined as 121 nGy h

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 38 publications
0
1
0
1
Order By: Relevance
“…From Table 2, it was observed that the mean RTOEGR dose rate of the New Market Thana in Dhaka city is lower than that of Iran, Chad, Nigeria, Turkey and higher than that of Egypt, India, Pakistan, Iraq. Furthermore, the mean RTOEGR dose rate of the New Market Thana in Dhaka city is comparable to that of Sabzevar city, Iran [38], Tribhuvan University, Nepal [43], Baghdad city, Iraq [54], Kirikkale city, Turkey [57].…”
Section: Dose Rate and Annual Effective Dosementioning
confidence: 96%
“…From Table 2, it was observed that the mean RTOEGR dose rate of the New Market Thana in Dhaka city is lower than that of Iran, Chad, Nigeria, Turkey and higher than that of Egypt, India, Pakistan, Iraq. Furthermore, the mean RTOEGR dose rate of the New Market Thana in Dhaka city is comparable to that of Sabzevar city, Iran [38], Tribhuvan University, Nepal [43], Baghdad city, Iraq [54], Kirikkale city, Turkey [57].…”
Section: Dose Rate and Annual Effective Dosementioning
confidence: 96%
“…Türkiye Atom Enerjisi Kurumu (TAEK) tarafından müsaade edilen radon konsantrasyonu limit değeri 400 Bq m -3 [12] olup elde ettiğimiz tüm değerler bu limit değerin altında kalmaktadır. Tablo 4'den görüldüğü gibi, bu çalışmada İstanbul için elde edilen ortalama radon aktivite konsantrasyonu Kestanbol [24], Kırklareli [26], Bayburt [28], Erzincan [18], Kırıkkale [30], Çankırı [32], Kilis [19] ve dünya ortalamasından [1] daha yüksektir.…”
Section: Bulgular Ve Tartışmaunclassified